Professores migrantes em Aracaju : múltiplas sociabilidades - Scardini, Maria Luisa (2008)
The process of urbanization in Brazil has acquired a new face, inserted in the new world migratory pattern, from the increase of population shifts to the cities of medium size, such as the capital of the state of Sergipe. The highly qualified people migration has caught attention. Considering the recent spread of higher education and expressive number of teachers from other cities in the country and even from abroad, this work is a result of a research done with a restricted group of migrant teachers who works in the two major universities in the state. 220 questionnaires were submitted and 10 interviews were held with teachers from various places of the country and with different personal characteristics. The results showed that most teachers came attracted by the opportunity to work and, secondarily, for the welfare that the city still offers. The research also approached the move generated from the cultural shock produced by migration, resulting in different strategies of acculturation and feelings of greater or lesser adaptation to the local society. Ambivalent feelings of the social construction of the foreign person were found in confrontation with other values and cultural practices. In that aspect, we have found strange views proper of the category searched on the culture and sociability.